The Uchuu simulations: Data Release 1 and dark matter halo concentrations. Issue 3 (22nd June 2021) - Ishiyama, Tomoaki; Prada, Francisco; Klypin, Anatoly A; Sinha, Manodeep; Metcalf, R Benton; Jullo, Eric; Altieri, Bruno; Cora, Sofía A; Croton, Darren; de la Torre, Sylvain; Millán-Calero, David E; Oogi, Taira; et al.
ABSTRACT: We introduce the Uchuu suite of large high-resolution cosmological N -body simulations. The largest simulation, named Uchuu, consists of 2.1 trillion (12 800 3 ) dark matter particles in a box of side-length 2.0 h^-1 Gpc, with particle mass of 3.27 × 10 8 h^-1 M_ . The highest resolution simulation, Shin-Uchuu, consists of 262 billion (6400 3 ) particles in a box of side-length 140 h^-1 Mpc, with particle mass of 8.97 × 10 5 h^-1 M_ . Combining these simulations, we can follow the evolution of dark matter haloes and subhaloes spanning those hosting dwarf galaxies to massive galaxy clusters across an unprecedented volume. In this first paper, we present basic statistics, dark matter power spectra, and the halo and subhalo mass functions, which demonstrate the wide dynamic range and superb statistics of the Uchuu suite. From an analysis of the evolution of the power spectra, we conclude that our simulations remain accurate from the baryon acoustic oscillation scale down to the very small. We also provide parameters of a mass–concentration model, which describes the evolution of halo concentration and reproduces our simulation data to within 5 per cent for haloes with masses spanning nearly eight orders of magnitude at redshift 0 ≤ z ≤ 14. There is an upturn in the mass–concentration relation for the population of all haloes and of relaxed haloes at z ≳ 0.5, whereas no upturn is detected at z < 0.5. We make publicly available various N -body products as part of Uchuu Data Release 1 on the Skies & Universes site. 1 Future releases will include gravitational lensing maps and mock galaxy, X-ray cluster, and active galactic nucleus catalogues.